Evaluating Antecedents of Online Customer Retention - Sohail, Hafsa; Tariq, Saroosh; Tariq, Anam (Pakistan Journal of Humanities and Social Sciences, 2023)
This study analyses and examines the impact of performance expectancy on online customer retention with the mediating role of customer satisfaction and experience. In this economic era, the mainstream trend is additionally making progress towards the organization by keeping up its positions. Consequently, it becomes necessary for organizations to give their first preferences to customers' tastes for the profitability of their organization. The study aims to unleash future research directions and recommendations to overcome the under-study problem. The target population of this study includes customers who shop online. The sample included 308 respondents who have experience in online purchasing. Sample selection was supported through non-probability sampling. Moreover, inferential statistics, i.e., correlation and regression analysis, were used to test the significance of the hypothesis statements. The findings of this research indicate that online customer retention has a significant positive relationship with the mediating role of experience and customer satisfaction. Furthermore, it will improve business, increase customer flow, and positively impact the company's profitability.